2004
DOI: 10.1002/nme.979
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of stress–strain relation using cone indentation: effect of friction

Abstract: SUMMARYAtkins and Tabor's approach (J. Mech. Phys. Solids 1965; 13:149) for predicting uniaxial stressstrain relation of metals from cone indentation tests has been studied using numerical (finite element) simulation of cone indentation. Two indentation parameters, namely representative strain and constraint factor, which are central to the prediction approach, have been estimated using the simulation for cone indenters of different apical angles. The effect of specimen-indenter interface friction on these par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…For a Vickers indenter, e r was estimated to be $8%, in agreement with the experimental results of Atkins and Tabor [31]. Recently, Cheng and Li [38] and Dicarlo et al [39] have performed FE simulations to determine e r for different conical indenters and validated these with the aid of the Atkins and Tabor [31] results. In addition, Dicarlo et al identified that friction between the indenter and sample has a significant influence on e r .…”
Section: Representative Strainmentioning
confidence: 70%
See 1 more Smart Citation
“…For a Vickers indenter, e r was estimated to be $8%, in agreement with the experimental results of Atkins and Tabor [31]. Recently, Cheng and Li [38] and Dicarlo et al [39] have performed FE simulations to determine e r for different conical indenters and validated these with the aid of the Atkins and Tabor [31] results. In addition, Dicarlo et al identified that friction between the indenter and sample has a significant influence on e r .…”
Section: Representative Strainmentioning
confidence: 70%
“…One reason could be due to the assumption of frictionless contact between the indenter and the sample, made while simulating the indentation response. The effect of friction on the plastic strain distribution is a widely debated topic in the literature [32,39,[57][58][59][60][61]. Dicarlo et al [39] have performed FE simulations of conical indentations for different values of the friction coefficient, l, between the indenter and the sample and then compared the simulation results with the experimental results of Atkins and Tabor [31].…”
Section: Strain Contours and Elastic-plastic Boundarymentioning
confidence: 98%
“…Despite this, three independent equations are required in the reverse analysis to estimate three mechanical properties E Ã ; Y; n. Therefore, dual or multiple indenters, which are expected to give more than two independent equations, have appeared as potential methods (Futakawa et al, 2001;Bucaille et al, 2003;Chollacoop et al, 2003;DiCarlo et al, 2004;Cao et al, 2005;Ogasawara et al, 2005Ogasawara et al, , 2006Swaddiwudhipong et al, 2005;Lan and Venkatesh, 2007;Luo and Lin, 2007;Yan et al, 2007;Le, 2008). Most of previous works used the concept of representative strain, which was originally introduced to interpret cone hardness by Atkins and Tabor (1965), to construct dimensionless relationships in instrumented sharp indentation.…”
Section: Introductionmentioning
confidence: 98%
“…Dual sharp indenter methods have been investigated in a number of studies to extract material properties (Bucaille et al, 2003;Chollacoop et al, 2003;DiCarlo et al, 2004;Cao et al, 2005;Ogasawara et al, 2005;Swaddiwudhipong et al, 2005;Ogasawara et al, 2006;Chen et al, 2007;Luo and Lin, 2007;Yan et al, 2007;Harsono et al, 2008;Le, 2008;Heinrich et al, 2009;Le, 2009). Dimensional analysis with the aid of finite element analysis (FEA) is widely used to explore various aspects of indentation, see the review by Cheng and Cheng (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Establishment of dimensionless functions, which capture the indentation response of materials, is a key issue to develop a systematic method for material characterization by instrumented indentation. Most of previous work used the concept of representative strain to construct dimensionless relationships in instrumented sharp indentation (Dao et al, 2001;Bucaille et al, 2003;Chollacoop et al, 2003;DiCarlo et al, 2004;Cao et al, 2005;Ogasawara et al, 2005Ogasawara et al, , 2006Chen et al, 2007;Ruan et al, 2010). The reduced elastic modulus-yield strength ratio E ⁄ /Y (or the elastic modulus-yield strength ratio E/Y) and the strain hardening exponent n were also investigated as two key parameters to govern indentation parameters (Swaddiwudhipong et al, 2005;Luo and Lin, 2007;Harsono et al, 2008;Heinrich et al, 2009).…”
Section: Introductionmentioning
confidence: 99%